Sistem Pendukung Keputusan Pemilihan Paket Indihome Terbaik Bagi Calon Pelanggan Menggunakan Metode Topsis (Studi Kasus PT. Telkom Indonesia Kandatel Binjai) - Riski Giofani; Marto Sihombing; Indah Ambarita (JUKI : Jurnal Komputer dan Informatika, 2022)
PT. Telkom Indonesia Kandatel Binjai provides various services (multi service) for its customers, namely voice (telephone), data (internet) and picture (IP-TV) services called indihome. Indihome products provide convenience in accessing the internet with different speeds, costs, quotas and needs. Prospective customers of PT. Telkom Indonesia Kandatel Binjai has problems in choosing the indihome service package package that its prospective customers want. Currently, prospective customers are faced with various choices of internet packages from indihome. With these various package options, prospective customers are required to be effective in choosing an internet package that suits their needs and purchasing power. To overcome this problem, a decision support system will be made using the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method which is expected to assist users in determining the choice of indihome packages that suit their needs. The criteria used are speed, number of devices, Fair Usage Policy (FUP), price, and type of service. Based on the test results using the TOPSIS method with 15 alternative data, the results obtained are the alternative A4 Regular Package Indihome 2P Internet 50 mbps + Telephone is an alternative that has the highest value compared to other alternatives